1997
DOI: 10.1115/1.2841100
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Large-Scale, High-Intensity Turbulence on Vane Aerodynamic Losses, Wake Growth, and the Exit Turbulence Parameters

Abstract: An experimental research program was undertaken to examine the influence of large-scale high-intensity turbulence on vane exit losses, wake growth, and exit turbulence characteristics. The experiment was conducted in a four-vane linear cascade at an exit Reynolds number of 800,000 based on chord length and an exit Mach number of 0.27. Exit measurements were made for four inlet turbulence conditions including a low-turbulence case (Tu ≈ 1 percent), a grid-generated turbulence case (Tu ≈ 7.5. percent) and two le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 16 publications
1
18
3
Order By: Relevance
“…Within investigations which generally involve low-speed turbine cascades [3,[59][60][61][62][63], a total pressure loss coefficient Ω = (P oi − P oe )/(P oi − P se ) is employed, which is equivalent to the Y P quantity given by (6). Within this definition, each term is generally determined locally at a particular spatial location.…”
Section: Omega Aerodynamic Loss Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within investigations which generally involve low-speed turbine cascades [3,[59][60][61][62][63], a total pressure loss coefficient Ω = (P oi − P oe )/(P oi − P se ) is employed, which is equivalent to the Y P quantity given by (6). Within this definition, each term is generally determined locally at a particular spatial location.…”
Section: Omega Aerodynamic Loss Coefficientsmentioning
confidence: 99%
“…Of these investigations, Hoheisel et al [1], Gregory-Smith and Cleak [2], and Ames and Plesniak [3] examine the influences of inlet turbulence on losses across turbine cascades. Hoheisel et al [1] also consider the effects of blade boundary layers, and Ames and Plesniak [3] demonstrate important connections between wake growth and level of freestream turbulence. Moore et al [4] indicate that more than one third of total losses develop downstream of airfoil trailing edges.…”
Section: Introductionmentioning
confidence: 99%
“…Gregory-Smith and Cleak [4] found grid turbulence increased profile losses by 7% but actually improved endwall losses due to the influence of the turbulence on the inlet boundary layer. Additionally, Ames and Plesniak [5] found that their 12% inlet turbulence, produced by a simulated combustor turbulence generator, caused significant "background" losses between the wakes which they attributed to the production of turbulence within the turbine vane passage and the redistribution of endwall losses by the turbulence. More recently, Mihelish and Ames [6] measured aerodynamic losses downstream from the present vane cascade and noted the impact of Reynolds number, turbulence condition, and Mach number on aerodynamic losses.…”
Section: Introductionmentioning
confidence: 98%
“…Considerable efforts are also devoted by many researchers in their experimental research programs for calibration and validation of different CFD models. Of the investigations which examine the effects of augmented free-stream turbulence levels, Ames and Plesniak [11] demonstrate important connections between freestream turbulence level and subsonic vane exit losses, wake growth, and wake turbulence characteristics. Radomsky and Thole [12] present measurements of time-averaged velocity components and Reynolds stresses along a turbine stator vane at elevated free-stream turbulence levels.…”
Section: Introductionmentioning
confidence: 98%